The role of environmental factors in developing obesity in children - Mazur, Artur; Dudek, Piotr (European Journal of Clinical and Experimental Medicine, 2010)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Childhood obesity poses one of the greatest challenges to pediatric health in the 21st century. De-veloping effective strategies for treatment and prevention is therefore a priority for clinical medicine and public health. This process is taking place at a time of unprecedented change in the understanding of the role of environmental factors in human health and disease, and environmental research into obesity has challenged assumptions about causal processes. The present paper is going to present current opi-nion on the role of environmental factors in the development childhood obesity.